The historical legacy of Norwegian mountain destinations: Current challenges and opportunities for development - Owusu, Kelvin; Tjørve, Even (Turyzm/Tourism, 2025)
This study explores the historical legacy of mountain destinations in the southeastern region of Norway to understand the challenges they face and their opportunities for development. It identifies exogenic (external) and endogenic (internal) factors that have influenced the destinations’ development from historical accounts in order to understand the different levels of success among them. The literature study and the emerging discussion are based on locally-sourced documents in order to bridge the gap between academic literature and little known or less available sources of destination history and development. The findings are that exogenic factors such as transportation, climate change and commodifiable slopes, which may primarily affect all destinations for alpine skiing but are not sufficient to determine the variation in success between them. Endogenic drivers such as ownership, management and leadership qualities strongly explain the different levels of success in a destination’s development. This study demonstrates those with favourable exogenic conditions struggle without effective endogenic drivers. Conversely, some destinations have overcome challenges from historical development and these are largely influenced by endogenic drivers. This research contributes a historical perspective of development that uncovers a range of underlying drivers, providing a framework for understanding how exogenic and endogenic factors shape mountain destinations’ success, sustainability and capacity to innovate.